2011
DOI: 10.1590/s0044-59672011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da distância entre iscas nas estimativas de abundância e riqueza de formigas em uma floresta de terra-firme na Amazônia Central

Abstract: RESUMOColetas com iscas são amplamente utilizadas para investigar a atividade de formigas de solo e vegetação e também podem ser empregadas para estimar o número de espécies e a abundância de formigas. Apesar de ser barata e fácil de implementar, a riqueza e abundância das formigas estimadas por iscas podem ser enviesadas por alguns fatores, como a distância entre iscas. Neste trabalho, avaliamos se a distância entre iscas altera as estimativas de abundância e riqueza de formigas e qual distância entre iscas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…This study shows that ant communities from disturbed forest areas are similar to those found in other Neotropical areas with some degree of environmental degradation. On the other hand, even with the subsampling approach of this study and the environmental degradation of forest areas highlighted by the presence of tramp ants in the fragments, species diversity of these areas is similar to others studies conducted with baits in relatively well preserved regions of the Amazonian rainforest (Baccaro et al 2011. In this sense, this work fills important gaps in the distribution of many ant species both native and exotic due to a lack of systematic surveys of biodiversity in the meridional Amazon.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study shows that ant communities from disturbed forest areas are similar to those found in other Neotropical areas with some degree of environmental degradation. On the other hand, even with the subsampling approach of this study and the environmental degradation of forest areas highlighted by the presence of tramp ants in the fragments, species diversity of these areas is similar to others studies conducted with baits in relatively well preserved regions of the Amazonian rainforest (Baccaro et al 2011. In this sense, this work fills important gaps in the distribution of many ant species both native and exotic due to a lack of systematic surveys of biodiversity in the meridional Amazon.…”
Section: Discussionsupporting
confidence: 82%
“…the previously defined areas, such as buildings, wood piles, construction waste, vegetation, rotting logs, twigs, and litter. Although the distance between the bait may have generated a subsampling (see Baccaro et al 2011), the complementarity of the methods may have minimized this problem, which is corroborated by the high diversity of ants sampled in this study.…”
Section: Lists Of Speciessupporting
confidence: 52%
“…Analyses of the accumulated richness curves indicated complete sampling of the ant fauna was not achieved in either type of trap, as none of the curves approached the asymptote. Thus, projected richness values were always greater than observed values (Table 1), which is the usual situation in biodiversity studies in the tropics (Martins & Santos, 1999;Feitosa & Ribeiro, 2005;Baccaro et al, 2011;Braga et al, 2010;Leponce et al, 2004;Delabie et al, 2007), since many rare species continue to be encountered even after extremely intense sampling efforts (Santos, 2003).…”
Section: Richness Estimatesmentioning
confidence: 82%
“…A distance of 20m between the sampling points was used for all of the collection methods to avoid pseudoreplication (Baccaro et al, 2011). Four ecosystem types with distinct phytophysiognomies were selected ( Table 1).…”
Section: Methodsmentioning
confidence: 99%